Research on magnetic regulation characteristics of axial-radial flux type permanent magnet synchronous machine - Cunxiang Yang; Kun Wang; Ziyang Liu; Bin Xiong; Qiang Zhao (Archives of Electrical Engineering, 2022)
Due to the fixed rotor magnetic field, the main magnetic flux of conventional permanent magnet synchronous motors (PMSMs) cannot be flexibly adjusted. Recently, the axial-radial flux type permanent magnet synchronous machine (ARFTPMSM) based on the hybrid excitation concept is proposed, which provides a new method for the speed and magnetic field regulations for PMSMs. To analyze the mechanism of magnetic field variation inside the ARFTPMSM, in this paper, three – dimensional finite element models for electromagnetic field calculation of the ARFTPMSM are established. On this basis, the influence of the axial device on the motor is discussed, and the mechanism of flux regulation is explained. By the quantitative calculation of air-gap flux density and the noload back-electromotive force (EMF), the flux regulation capability of the ARFTPMSM is verified. In addition, the effect of the excitation magnetomotive force on the magnetic field harmonics is analyzed combined with the winding theory, and the influence of the axial magneto-motive force (MMF) on the torque fluctuation is obtained. The flux regulation performance of the motor and the validity of the numerical calculation analysis are verified by the experiments.